Hydrogen deuterium exchange mass spectrometry identifies the dominant paratope in CD20 antigen binding to the NCD1.2 monoclonal antibody. Issue 1 (15th January 2021) - Uhrik, Lukas; Hernychova, Lenka; Muller, Petr; Kalathiya, Umesh; Lisowska, Malgorzata M.; Kocikowski, Mikolaj; Parys, Maciej; Faktor, Jakub; Nekulova, Marta; Nortcliffe, Chris; Zatloukalova, Pavlina; Ruetgen, Barbara; et al.
Abstract : A comparative canine–human therapeutics model is being developed in B-cell lymphoma through the generation of a hybridoma cell that produces a murine monoclonal antibody specific for canine CD20. The hybridoma cell produces two light chains, light chain-3, and light chain-7. However, the contribution of either light chain to the authentic full-length hybridoma derived IgG is undefined. Mass spectrometry was used to identify only one of the two light chains, light chain-7, as predominating in the full-length IgG. Gene synthesis created a recombinant murine–canine chimeric monoclonal antibody expressing light chain-7 that reconstituted the IgG binding to CD20. Using light chain-7 as a reference sequence, hydrogen deuterium exchange mass spectrometry was used to identify the dominant CDR region implicated in CD20 antigen binding. Early in the deuteration reaction, the CD20 antigen suppressed deuteration at CDR3 (VH ). In later time points, deuterium suppression occurred at CDR2 (VH ) and CDR2 (VL ), with the maintenance of the CDR3 (VH ) interaction. These data suggest that CDR3 (VH ) functions as the dominant antigen docking motif and that antibody aggregation is induced at later time points after antigen binding. These approaches define a methodology for fine mapping of CDR contacts using nested enzymatic reactions and hydrogen deuterium exchange mass spectrometry. These data support the further development of an engineered, synthetic canine–murine monoclonal antibody, focused on CDR3 (VH ), for use as a canine lymphoma therapeutic that mimics the human–murine chimeric anti-CD20 antibody Rituximab.